Expression Profiles of Circular RNA in Aortic Vascular Tissues of Spontaneously Hypertensive Rats - Liu, Ying; Dong, Ying; Dong, Zhaojie; Song, Jiawei; Zhang, Zhenzhou; Liang, Lirong; Liu, Xiaoyan; Sun, Lanlan; Li, Xueting; Zhang, Miwen; Chen, Yihang; Miao, Ran; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Circular RNAs (circRNAs), as a kind of endogenous non-coding RNA, have been implicated in ischemic heart diseases and vascular diseases. Based on theirs high stability with a closed loop structure, circRNAs function as a sponge and bind specific miRNAs to exert inhibitory effects in heart and vasculature, thereby regulating their target gene and protein expression, via competitive endogenous RNA (ceRNA) mechanism. However, the exact roles and underlying mechanisms of circRNAs in hypertension and related cardiovascular diseases remain largely unknown. Methods and Results: High-throughput RNA sequencing (RNA-seq) was used to analyze the differentially expressed (DE) circRNAs in aortic vascular tissues of spontaneously hypertensive rats (SHR). Compared with the Wistar-Kyoto (WKY) rats, there were marked increases in the levels of systolic blood pressure, diastolic blood pressure and mean blood pressure in SHR under awake conditions via the tail-cuff methodology. Totally, compared with WKY rats, 485 DE circRNAs were found in aortic vascular tissues of SHR with 279 up-regulated circRNAs and 206 down-regulated circRNAs. Furthermore, circRNA-target microRNAs (miRNAs) and the target messenger RNAs (mRNAs) of miRNAs were predicted by the miRanda and Targetscan softwares, respectively. Additionally, real-time RT-PCR analysis verified that downregulation of rno_circRNA_0009197, and upregulation of rno_circRNA_0005818, rno_circRNA_0005304, rno_circRNA_0005506, and rno_circRNA_0009301 were observed in aorta of SHR when compared with that of WKY rats. Then, the potential ceRNA regulatory mechanism was constructed via integrating 5 validated circRNAs, 31 predicted miRNAs, and 266 target mRNAs. More importantly, three hub genes (NOTCH1, FOXO3, and STAT3) were recognized according to PPI network and three promising circRNA-miRNA-mRNA regulatory axes were found in hypertensive rat aorta, including rno_circRNA_0005818/miR-615/NOTCH1, rno_circRNA_0009197/ miR-509-5p/FOXO3, and rno_circRNA_0005818/miR-10b-5p/STAT3, respectively. Conclusions: Our results demonstrated for the first time that circRNAs are expressed aberrantly in aortic vascular tissues of hypertensive rats and may serve as a sponge linking with relevant miRNAs participating in pathogenesis of hypertension and related ischemic heart diseases via the circRNA-miRNA-mRNA ceRNAnetwork mechanism.